An HIV Prevention Protocol Reviewed at 15 National Sites: How do Ethics Committees Protect Communities? - Deeds, Bethany Griffin; Castillo, Marné; Beason, Zephyr; Cunningham, Shayna D.; Ellen, Jonathan M.; Peralta, Ligia (Journal of empirical research on human research ethics, 2008)
TO LEARN WHETHER ETHICS COMMITTEES reviewing community-based participatory research concentrate on the protection of communities, in addition to individual participants, data from 15 sites were analyzed. Eighty-two ethics committee concerns related to consent (35%), protocol procedures (49%), data collection (17%), and HIPAA (6%) were identified. Concerns generally involved individual level subject issues; only 17% were related to community issues. To improve community-level protections in research, the authors recommend that both ethics committee members and research staff receive education concerning protection and respect for communities, that a community member group be established to advise researchers throughout the planning and implementation of community-level studies and that local ethics committee boards include members with community-level experience.